Genomic insights into the evolution, pathogenicity, and extensively drug-resistance of emerging pathogens Kluyvera and Phytobacter - Huang, Zhenzhou; Zhang, Guozhong; Zheng, Zhibei; Lou, Xiuqin; Cao, Feifei; Zeng, Lingyi; Wang, Duochun; Yu, Keyi; Li, Jun (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Kluyvera is a Gram-negative, flagellated, motile bacillus within the Enterobacteriaceae. The case reports of clinical infections shed light on the importance of this organism as an emerging opportunistic pathogen. The genus Phytobacter, which often be misidentified with Kluyvera, is also an important clinically relevant member of the Enterobacteriaceae. However, the identification of Kluyvera and Phytobacter is problematic, and their phylogenetic relationship remains unclear. Methods Here, 81 strains of Kluyvera and 16 strains of Phytobacter were collected. A series of comparative genomics approaches were applied to the phylogenetic relationship reconstruction, virulence related genes profiles description, and antibiotic resistance genes prediction. Results Using average nucleotide identity (ANI) and in silico DNA-DNA hybridization (isDDH), we offered reliable species designations of 97 strains, in which 40 (41.24%) strains were incorrectly labeled. A new Phytobacter genomospecies-1 were defined. Phytobacter and Kluyvera show great genome plasticity and inclusiveness, which may be related to their diverse ecological niches. An intergenomic distances threshold of 0.15875 was used for taxonomy reassignments at the phylogenomic-group level. Further principal coordinates analysis (PCoA) revealed 11 core genes of Kluyvera (pelX, mdtL, bglC, pcak-1, uhpB, ddpA-2, pdxY, oppD-1, cptA, yidZ, csbX) that could be served as potential identification targets. Meanwhile, the Phytobacter specific virulence genes clbS, csgA-C, fliS, hsiB1_vipA and hsiC1_vipB, were found to differentiate from Kluyvera. We concluded that the evolution rate of Kluyvera was 5.25E-6, approximately three times higher than that of Phytobacter. Additionally, the co-existence of ESBLs and carbapenem resistance genes were present in approximately 40% strains, suggesting the potential development of extensively drug-resistant or even fully drug-resistant strains. Discussion This work provided a better understanding of the differences between closely related species Kluyvera and Phytobacter. Their genomes exhibited great genome plasticity and inclusiveness. They not only possess a potential pathogenicity threat, but also a risk of multi-drug resistance. The emerging pathogens Kluyvera and Phytobacter warrant close attention.